Endophytic Bacterium Serratia plymuthica From Chinese Leek Suppressed Apple Ring Rot on Postharvest Apple Fruit - Sun, Meng; Liu, Junping; Li, Jinghui; Huang, Yonghong (Frontiers in Microbiology, 2022)
Apple ring rot caused by Botryosphaeria dothidea is an economically significant plant disease that spreads across the apple production areas in China. The pathogen infects apple fruits during the growing season and results in postharvest fruits rot during storage, which brings about a huge loss to plant growers. The study demonstrated that an endophytic bacterium Serratia plymuthica isolated from Chinese leek (Allium tuberosum) significantly suppressed the mycelial growth, severely damaging the typical morphology of B. dothidea, and exerted a high inhibition of 84.64% against apple ring rot on postharvest apple fruit. Furthermore, S. plymuthica significantly reduced the titratable acidity (TA) content, enhanced the soluble sugar (SS) content, vitamin C content, and SS/TA ratio, and maintained the firmness of the fruits. Furthermore, comparing the transcriptomes of the control and the S. plymuthica treated mycelia revealed that S. plymuthica significantly altered the expressions of genes related to membrane (GO:0016020), catalytic activity (GO:0003824), oxidation-reduction process (GO:0055114), and metabolism pathways, including tyrosine metabolism (ko00280), glycolysis/gluconeogenesis (ko00010), and glycerolipid metabolism (ko00561). The present study provided a possible way to control apple ring rot on postharvest fruit and a solid foundation for further exploring the underlying molecular mechanism.